2020
DOI: 10.1186/s12967-020-02459-w
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin prevents necrotizing enterocolitis in very preterm infants: a randomized controlled trial

Abstract: Background: Necrotizing enterocolitis (NEC) is one of the most severe complications in very preterm infants, but there are currently no accepted methods to prevent NEC. Studies have shown that erythropoietin (EPO) has the potential to prevent NEC or improve outcomes of preterm NEC. This study aimed to determine whether recombinant human EPO (rhEPO) could protect against NEC in very preterm infants. Methods: The study was a prospective randomized clinical trial performed among four NICU centers. A total of 1327… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 55 publications
(84 reference statements)
1
31
1
Order By: Relevance
“…GA was established based on first-trimester ultrasound estimations in the majority of patients and in a few patients by the last menstrual bleeding before pregnancy. The following parameters were included in the analysis: small for gestational age (SGA, defined as birth weight < 10th percentile for gestational age), asphyxia ( 14 ), bronchopulmonary dysplasia (BPD, defined simply by considering the need for oxygen at 28 days after birth) ( 15 ), pneumonia, anemia ( 16 ), patent ductus arteriosus ( 17 ), persistent pulmonary hypertension ( 18 ), coagulopathy ( 19 ), retinopathy of prematurity ( 20 ), necrotizing enterocolitis (NEC, Bell's stage ≥ II) ( 16 ), intraventricular hemorrhage (IVH, diagnosed by intracranial ultrasound and graded from 1 to 4 on the Papile scale) ( 21 ), periventricular leukomalacia (PVL, diagnosed by intracranial ultrasound or brain magnetic resonance imaging) ( 22 ), pathoglycemia (blood sugar < 2.2 mmol/L or > 7 mmol/L), and neonatal death (died before 28 days of life).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…GA was established based on first-trimester ultrasound estimations in the majority of patients and in a few patients by the last menstrual bleeding before pregnancy. The following parameters were included in the analysis: small for gestational age (SGA, defined as birth weight < 10th percentile for gestational age), asphyxia ( 14 ), bronchopulmonary dysplasia (BPD, defined simply by considering the need for oxygen at 28 days after birth) ( 15 ), pneumonia, anemia ( 16 ), patent ductus arteriosus ( 17 ), persistent pulmonary hypertension ( 18 ), coagulopathy ( 19 ), retinopathy of prematurity ( 20 ), necrotizing enterocolitis (NEC, Bell's stage ≥ II) ( 16 ), intraventricular hemorrhage (IVH, diagnosed by intracranial ultrasound and graded from 1 to 4 on the Papile scale) ( 21 ), periventricular leukomalacia (PVL, diagnosed by intracranial ultrasound or brain magnetic resonance imaging) ( 22 ), pathoglycemia (blood sugar < 2.2 mmol/L or > 7 mmol/L), and neonatal death (died before 28 days of life).…”
Section: Methodsmentioning
confidence: 99%
“…GA was established based on first-trimester ultrasound estimations in the majority of patients and in a few patients by the last menstrual bleeding before pregnancy. The following parameters were included in the analysis: small for gestational age (SGA, defined as birth weight < 10th percentile for gestational age), asphyxia (14), bronchopulmonary dysplasia (BPD, defined simply by considering the need for oxygen at 28 days after birth) (15), pneumonia, anemia (16), patent ductus arteriosus (17), persistent pulmonary hypertension (18), coagulopathy (19), retinopathy of prematurity (20)…”
Section: Definition and Data Collectionmentioning
confidence: 99%
“…In addition, Patel [17] performed a multicenter cohort study in 598 VLBW infants and found that severe anemia but not RBC transfusion was associated with an increased risk of NEC. Our previous clinical trial found that the improvement of severe anemia reduced the incidence of NEC in preterm infants, which also suggested the impact of anemia on the development of NEC [19]. A prospective cohort study showed that anemia was associated with intestinal injury [33].…”
Section: Discussionmentioning
confidence: 95%
“…Some studies highlighted that severe anemia, not the transfusion event, was associated with the risk of developing NEC [17,18]. Our previous study [19] indicated that erythropoietin treatment for severe anemia could decrease the incidence of NEC in preterm infants, which indirectly proves the association between severe anemia and NEC. Animal models suggested that anemia can induce intestinal inflammation and barrier disruption, and increase the risk for NEC [20,21].…”
Section: Introductionmentioning
confidence: 83%
“…Baseline information were collected, including gestational age, birth weight, sex, delivery mode, Apgar score, mechanical ventilation, and maternal factors during the perinatal period. Complications during hospitalization such as retinopathy of prematurity (ROP) [ 31 ], necrotizing enterocolitis (NEC) [ 32 ], and bronchopulmonary dysplasia (BPD) [ 33 ] were recorded. Infants who developed rhEPO-related side effects, including large venous thrombus, polycythemia, or hypertension, were immediately taken off the rhEPO treatment and given emergency therapy.…”
Section: Methodsmentioning
confidence: 99%